A conceptual model: Continuance intention of mobile banking among Malaysian customers - Mohtar, Shahimi; Abdul Rani, Nurdiana; Ariffin, Ahmad Shabudin (2018)
In the research field of mobile banking, attention is focused on customers‟ adoption of mobile banking.However, the expected benefits of a given IT cannot be realized and its implementation cannot be considered successful if its usage is not sustained over the long-term by the users who are expected to benefits from its usage.In this paper, through contrasting the dimensions of customers‟ trust and factors that affect the mobile banking customer‟s behaviour, this study proposes the dimensions of mobile banking customer‟s trust and the conceptions of these dimensions.Based on the key conception of mobile banking customers‟ trust, this study extends the expectation-confirmation model for information technology and build a conceptual model of mobile banking customers‟ continuance intention.